The bi-factor structure of the 17-item Hamilton Depression Rating Scale in persistent major depression; dimensional measurement of outcome - Nixon, Neil (PLoS One, 2020)
BACKGROUND: The 17-item Hamilton Depression Rating Scale (HDRS(17)) is used world-wide as an observer-rated measure of depression in randomised controlled trials (RCTs) despite continued uncertainty regarding its factor structure. This study investigated the dimensionality of HDRS(17) for patients undergoing treatment in UK mental health settings with moderate to severe persistent major depressive disorder (PMDD). METHODS: Exploratory Structural Equational Modelling (ESEM) was performed to examine the HDRS(17) factor structure for adult PMDD patients with HDRS(17) score ≥16. Participants (n = 187) were drawn from a multicentre RCT conducted in UK community mental health settings evaluating the outcomes of a depression service comprising CBT and psychopharmacology within a collaborative care model, against treatment as usual (TAU). The construct stability across a 12-month follow-up was examined through a measurement equivalence/invariance (ME/I) procedure via ESEM. RESULTS: ESEM showed HDRS(17) had a bi-factor structure for PMDD patients (baseline mean (sd) HDRS(17) 22.6 (5.2); 87% PMDD >1 year) with an overall depression factor and two group factors: vegetative-worry and retardation-agitation, further complicated by negative item loading. This bi-factor structure was stable over 12 months follow up. Analysis of the HDRS(6) showed it had a unidimensional structure, with positive item loading also stable over 12 months. CONCLUSIONS: In this cohort of moderate-severe PMDD the HDRS(17) had a bi-factor structure stable across 12 months with negative item loading on domain specific factors, indicating that it may be more appropriate to multidimensional assessment of settled clinical states, with shorter unidimensional subscales such as the HDRS(6) used as measures of change.